Rib-sparing scalenotomy in thoracic outlet syndrome treatment: A systematic review and meta-analysis - Ruopsa, Niina; Vastamäki, Heidi; Vahlberg, Tero; Vastamäki, Martti; Ristolainen, Leena (SAGE PUBLICATIONS LTD, 2025)
Background and Aims: The majority of neurogenic thoracic outlet syndrome (NTOS) surgery still involves removal of the first rib. A rib-sparing procedure has also been found to give a good result, but no meta-analysis has been published about this procedure. Also, from a financial point of view, it is important to know what kind of results have been obtained in the treatment of NTOS with rib-sparing surgery. Our opinion is that first-rib resection (FRR) surgeries, which contain more complications and require a longer recovery time, are performed too often these days, if the same result is achieved with rib-sparing surgery.
Methods: We accomplished a systematic review and meta-analysis to find out the outcome of rib-sparing NTOS surgery, collecting studies on rib-sparing supraclavicular scalenotomy in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines using appropriate databases.
Results: Of 1354 studies, 18 studies met our inclusion criteria. The mean study sample size was 58, and the mean patient age at surgery was 35.8 years. All studies reported long-term outcomes, with the mean follow-up time of 49 months. All reported fewer patient complaints after surgical TOS treatment. In our meta-analysis, improvement to Derkash's excellent/good classifications was achieved in 71% (95% confidence interval (CI) = 64.4% to 76.4%, I2 = 73.0%). The heterogeneity noted in the systematic review showed no significant moderation by gender, age, or follow-up time. The studies included had a low risk of publication bias, with most failing to use validated evaluation methods.
Conclusion: According to this analysis, the rib-sparing surgical treatment of NTOS is beneficial to most patients and relatively safe. Still, future studies should accommodate validated thoracic outlet scales
Type of study / level of evidence: Therapeutic IV